If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 2 + -4y = 1x + -4 Reorder the terms: 2 + 3x + -4y = 1x + -4 Reorder the terms: 2 + 3x + -4y = -4 + 1x Solving 2 + 3x + -4y = -4 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 2 + 3x + -1x + -4y = -4 + 1x + -1x Combine like terms: 3x + -1x = 2x 2 + 2x + -4y = -4 + 1x + -1x Combine like terms: 1x + -1x = 0 2 + 2x + -4y = -4 + 0 2 + 2x + -4y = -4 Add '-2' to each side of the equation. 2 + 2x + -2 + -4y = -4 + -2 Reorder the terms: 2 + -2 + 2x + -4y = -4 + -2 Combine like terms: 2 + -2 = 0 0 + 2x + -4y = -4 + -2 2x + -4y = -4 + -2 Combine like terms: -4 + -2 = -6 2x + -4y = -6 Add '4y' to each side of the equation. 2x + -4y + 4y = -6 + 4y Combine like terms: -4y + 4y = 0 2x + 0 = -6 + 4y 2x = -6 + 4y Divide each side by '2'. x = -3 + 2y Simplifying x = -3 + 2y
| 4x-3(x+1)=2(x-1)-16 | | 4y-x=12 | | 3y+20=5 | | 2(y-3x)=16-12x | | 11=44x-11y | | 8u+21=45 | | (X-4)=3x+2 | | 3-5x+9=25 | | f(x)=5x^2+bx+c | | f(x)=-7x^2+28x+25 | | 6x=27y-3 | | (6*6)*(4*4*4)= | | 5(X-13)-7(6-X)+29=50-3(8-X) | | a+(a-8)=44 | | %.317=164 | | x^2+6.91830971e-7x-4e-8=0 | | x^2-3x/7x | | p+(-4)=1 | | 1a(105/(35/7)) | | 8x+8=9x-7 | | 3x+2x-5=x+7 | | 1/4×16 | | x^2+x-0.058=0 | | 48/165 | | 1/3(9x-12)=1/4(16x-12) | | 2x-5=3x-16 | | X/22=15/33 | | x+(x+1)+(x+2)=(x+3)+100 | | x+(x+1)+(x+2)=100 | | x-4=-x+6 | | 12/x=3/10 | | 3(7+10)+4(7+20)+5(7)=185-3(7) |